Predictors of frequent emergency department visits among rural older adults in Ontario using the Resident Assessment Instrument‐Home Care. (29th June 2015) - Neufeld, Eva; Viau, Katelynn A.; Hirdes, John P.; Warry, Wayne
Abstract: Objective: To describe factors predicting frequent emergency department (ED) use among rural older adults receiving home care services in Ontario, Canada. Design: A cross‐sectional examination of Ontario hospital administrative data linked to provincial home care data compares frequent ED users (i.e. >4 visits/year) with regular users (i.e. 1–3 visits/year) and no ED use over a 1‐year period. Multiple logistic regression analysis was performed using independent variables from home care health assessments. Main outcome measures: Predictors of frequent ED use among rural older adults receiving home care services using adjusted odds ratios (ORs) and 95% confidence intervals (CI). Results: Ontario's rural home care clients visited the ED an average of 4.9 times (SD = 11.9) over a year. Frequent ED users were observed in 170 cases per 1000 home care clients. Congestive heart failure was the most frequently cited reason for frequent ED use; however, it was not a main driver in the adjusted model. Frequent ED use was predicted by younger age (i.e. 60–74 years) (OR = 1.9; 95% CI, 1.7–2.2), a recent ED visit in the last 3 months (OR = 1.5; 95% CI, 1.4–1.7), regularly taking >9 medications (OR = 1.5; 95% CI, 1.3–1.6), and poor self‐rated health (OR = 1.4; 95% CI, 1.2–1.5). Conclusion: Despite popular assumptions, the main drivers for frequent ED use among rural older adults in Ontario included a mix of sociodemographic and clinical characteristics, rather than disease diagnoses.